2021
DOI: 10.1017/jns.2021.69
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational differences in dietary acculturation among Ghanaian immigrants living in New York City: a qualitative study

Abstract: Dietary acculturation may explain the increasing risk of diet-related diseases among African immigrants in the United States (US). We interviewed twenty-five Ghanaian immigrants (Youth n 13, Age (Mean ± sd) 20 y ± 5⋅4, Parents (n 6) and Grandparents (n 6) age 58⋅7 ± 9⋅7) living in New York City (NYC) to (a) understand how cultural practices and the acculturation experience influence dietary patterns of Ghanaian immigrants and (b) identify intergenerational differences in dietary acculturation among Ghanaian yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Second, these variables only permit a simplistic comparison of foreign-born to US-born Black-identifying adults, which does not capture the generational effects associated with immigration. Studies have found intergenerational differences in dietary change among West-African immigrants, with first-generation West-African adults exhibiting more dietary acculturation compared to their immigrant parents [ 36 ]. NHANES data do not provide data to determine their generational status.…”
Section: Discussionmentioning
confidence: 99%
“…Second, these variables only permit a simplistic comparison of foreign-born to US-born Black-identifying adults, which does not capture the generational effects associated with immigration. Studies have found intergenerational differences in dietary change among West-African immigrants, with first-generation West-African adults exhibiting more dietary acculturation compared to their immigrant parents [ 36 ]. NHANES data do not provide data to determine their generational status.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have been conducted in European and North American countries to assess the post-migration changes in diet and lifestyle among immigrant communities [ 2 , 3 , 4 , 5 , 6 , 9 , 10 , 11 ], not many studies have been conducted in Asian countries. Particularly, East Asian countries such as Japan, China, and South Korea have become popular destinations among migrants in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…According to a national survey conducted in 2022, 20.2% (estimated 21.30 million) of the adult Japanese population were active participants in sports and physical activities, with about 30% ‘strolling’ or ‘walking’, while about 15% were engaged in ‘calisthenics and light exercises’ and ‘weight training’ [ 17 ]. As the adaptation to a less healthy American diet leads to increased chronic diseases among migrants in the United States [ 10 , 11 ], it would be intriguing to assess the changes in dietary patterns among foreign residents in Japan. It was also our interest to investigate how the PA of migrants changes when they navigate their life in Japan.…”
Section: Introductionmentioning
confidence: 99%